Hill magars and their neighbours: hill peoples surrounding the Ganges plain - Jiro,Kawakita (Tokyo, 1974)
The book presented here is Volume III of a series of academic reports on anthropological fieldwork, "Synthetic Research on Rice-cultivating peo ples in Southeast Asian Countries", sponsored by the Japanese Society of Ethnology. Preceding this volume, two volumes appeared successively: SUGI YAMA Koichi (1969): A Study of the Mundas Village Life in India and YAMADA Ryuji (1970): Cultural Formation of the Mundas, both of which were the second and first volume respectively of the series Hill Peoples Surrounding the Ganges Plain, edited by KAWAKITA Jiro.
Keywords: Community development